When Bell's Palsy Is Cancer: Avoiding Misdiagnosis and Its Implications - Wen, Y. Edward; Rail, Benjamin; Sanchez, Cristina V.; Gorman, April R.; Rozen, Shai M. (Journal of Reconstructive Microsurgery, 2024)
Background Facial paralysis due to cancer can be misdiagnosed as Bell's palsy. This study aims to clearly identify and quantify diagnostic differentiators and further evaluate the prognostic implications of misdiagnosis.Methods Adult patients older than 18 years with facial palsy of unknown or cancerous etiology presenting between 2009 and 2023 were reviewed. Patient characteristics, examination findings, and clinical course were compared between facial paralysis patients with cancer misdiagnosed as Bell's palsy (Cancer-Bell's-Palsy group) and patients correctly diagnosed with Bell's palsy (Bell's-Palsy group). Additionally, morbidity and mortality were compared between facial paralysis patients with cancer initially misdiagnosed with Bell's palsy and facial paralysis patients initially correctly diagnosed with cancer (Cancer-Palsy group).Results Two-hundred and forty-three patients participated including 43 Cancer-Palsy, 18 Cancer-Bell's-Palsy, and 182 Bell's-Palsy patients. Cancer-Bell's-Palsy patients were significantly less likely than Bell's-Palsy patients to develop synkinesis (odds ratio [OR] = 0.0042; 95% confidence interval [CI]: [0.0005–0.0339]; p < 0.0001), significantly more likely to experience gradual onset facial paralysis (OR = 1,004.69; 95% CI: [54.40–18,555.77]; p < 0.0001), and significantly more likely to have additional nonfacial cranial nerve neuropathies (OR = 49.98; 95% CI: [14.61–170.98]; p < 0.0001). Cancer-Bell's-Palsy patients were more likely than Cancer-Palsy patients to have a greater than 6-month period from initial cancer-attributable symptom onset to cancer diagnosis (OR = 47.62; 95% CI: [9.26–250.00]; p < 0.001), stage IV cancer (OR: 12.36; 95% CI: 1.49–102.71; p = 0.006), and decreased duration of life after cancer diagnosis (median [interquartile range], 40.0 [87.0] vs. 12 [56.3] months, respectively; p = 0.025).Conclusion Facial paralysis related to cancer must be differentiated from Bell's palsy, as misdiagnosis leads to delayed intervention and poorer prognosis. Gradual onset facial palsy, multiple cranial nerve neuropathies, lack of synkinesis, and lack of improvement were nearly definitive differentiators for underlying cancer.
Keywords: facial palsy; cancer; Bell's palsy